2016
DOI: 10.1371/journal.pone.0146813
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory Posturing of the Vocal Tract Reveals Dissociation of Speech Movement Plans from Linguistic Units

Abstract: Models of speech production typically assume that control over the timing of speech movements is governed by the selection of higher-level linguistic units, such as segments or syllables. This study used real-time magnetic resonance imaging of the vocal tract to investigate the anticipatory movements speakers make prior to producing a vocal response. Two factors were varied: preparation (whether or not speakers had foreknowledge of the target response) and pre-response constraint (whether or not speakers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…We might expect speakers with a planned but withheld acoustic utterance to position articulators at or near relevant target positions. Laboratory research in the delayed naming paradigm has confirmed that this is indeed what speakers do (Kawamoto, Liu, Mura, & Sanchez, 2008; Tilsen et al, 2016).…”
Section: Regulating the Flow Of Planned Syllablesmentioning
confidence: 74%
See 3 more Smart Citations
“…We might expect speakers with a planned but withheld acoustic utterance to position articulators at or near relevant target positions. Laboratory research in the delayed naming paradigm has confirmed that this is indeed what speakers do (Kawamoto, Liu, Mura, & Sanchez, 2008; Tilsen et al, 2016).…”
Section: Regulating the Flow Of Planned Syllablesmentioning
confidence: 74%
“…Speakers generally interpret the instructions as prohibiting acoustic speech prior to the “go” signal, but not as prohibiting silent articulation. When not specifically instructed to avoid early articulation, speakers move their lips (Kawamoto et al, 2008) and various internal articulators (Tilsen et al, 2016) into position. The early postures are target‐specific, rather than reflecting a general readiness for speech (Tilsen et al, 2016).…”
Section: Regulating the Flow Of Planned Syllablesmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been recently done, for example, by Narayanan et al (2014; 10 speakers of American English) and Barlaz et al (2018; 12 speakers of Brazilian Portuguese). Of note are also the exceptionally large‐sample studies by Tilsen et al (2016; 25 speakers of American English) and Dediu & Moisik (2019; 80 L1 and L2 speakers of English), both of which were not part of the above survey (see Footnote 1).…”
Section: Entire Vocal Tractmentioning
confidence: 98%